1α, 25-Dihydroxyvitamin D3 promotes CD200 expression by human peripheral and airway-resident T cells. Issue 7 (14th February 2012) - Dimeloe, Sarah; Richards, David F; Urry, Zoe L; Gupta, Atul; Stratigou, Victoria; Farooque, Sophie; Saglani, Sejal; Bush, Andrew; Hawrylowicz, Catherine M
Abstract : Background: CD200, a cell-surface immunoglobulin-like molecule expressed by immune and stromal cells, dampens the pro-inflammatory activity of tissue-resident innate cells via its receptor, CD200R. This interaction appears critical for peripheral immune tolerance, particularly in the airways where excessive inflammation is undesirable. Vitamin D contributes to pulmonary health and promotes regulatory immune pathways, therefore its influence on CD200 and CD200R was investigated. Methods: CD200 and CD200R expression were assessed by qPCR and immunoreactivity of human lymphoid, myeloid and epithelial cells following 1α, 25-dihydroxyvitamin D3 (1α, 25VitD3) exposure in vitro and in peripheral T cells following 1α, 25VitD3 oral ingestion in vivo. The effect of 1α25VitD3 was also assessed in human airway-resident cells. Results: 1α25VitD3 potently upregulated CD200 on peripheral human CD4+ T cells in vitro, and in vivo there was a trend towards upregulation in healthy, but not asthmatic individuals. CD200R expression was not modulated in any cells studied. CD200 induction was observed to a lesser extent in CD8+ T cells and not in B cells or airway epithelium. T cells isolated from the human airway also responded strongly to 1α25VitD3 to upregulate CD200. Conclusions: The capacity of 1α, 25-dihydroxyvitamin D3 to induce CD200 expression by peripheral and respiratory tract T cells identifies an additional pathway via which vitamin D can restrain inflammation in the airways to maintain respiratory health.